KOMPETENSI GURU IDEAL PERSPEKSTIF AL-ZARNUJI - Suriani (Jurnal Payung Sekaki : Kajian Keislaman, 2024)
Competence is an absolute thing that must be possessed by teachers, because teachers have a big share in the educational process, especially in achieving educational success. One of the Muslim leaders who has explained the concept of competence that must be owned by the teacher is Al-Zarnuji in the book of Ta'lim al-Muta'allim, then this study aims to determine the concept of teacher competence according to Al-Zarnuji in the book of Ta'lim al-Muta'allim. To determine the competencies of teachers according to law No.14 of 2005 on teachers and lecturers. To determine the relevance of teacher competence according to Al-Zarnuji in the book of Ta'lim Al-Muta'allim with law No.14 of 2005 on teachers and lecturers. The approach used is a qualitative descriptive approach to the type of library research (library research). Primary sources in this study is the book of Ta'lim Al-Muta'allim by Al-Zarnuji and Law No.14 of 2005 on teachers and lecturers and secondary sources are writings and research on teacher competence. Data collection techniques in this study is the library. Data analysis techniques in this study is to use the data analysis model “Content Analysis